Lake and drained lake basin systems in lowland permafrost regions - Jones, Benjamin M.; Grosse, Guido; Farquharson, Louise M.; Roy-Léveillée, Pascale; Veremeeva, Alexandra; Kanevskiy, Mikhail Z.; Gaglioti, Benjamin V.; Breen, Amy L.; Parsekian, Andrew D.; Ulrich, Mathias; Hinkel, Kenneth M (Nature Reviews Earth & Environment, 2022)
The formation, growth and drainage of lakes in Arctic and boreal lowland permafrost regions influence landscape and ecosystem processes. These lake and drained lake basin (L-DLB) systems occupy >20% of the circumpolar Northern Hemisphere permafrost region and ~50% of the area below 300 m above sea level. Climate change is causing drastic impacts to L-DLB systems, with implications for permafrost dynamics, ecosystem functioning, biogeochemical processes and human livelihoods in lowland permafrost regions. In this Review, we discuss how an increase in the number of lakes as a result of permafrost thaw and an intensifying hydrologic regime are not currently offsetting the land area gained through lake drainage, enhancing the dominance of drained lake basins (DLBs). The contemporary transition from lakes to DLBs decreases hydrologic storage, leads to permafrost aggradation, increases carbon sequestration and diversifies the shifting habitat mosaic in Arctic and boreal regions. However, further warming could inhibit permafrost aggradation in DLBs, disrupting the trajectory of important microtopographic controls on carbon fluxes and ecosystem processes in permafrost-region L-DLB systems. Further research is needed to understand the future dynamics of L-DLB systems to improve Earth system models, permafrost carbon feedback assessments, permafrost hydrology linkages, infrastructure development in permafrost regions and the well-being of northern socio-ecological systems.